2016
DOI: 10.1515/ethemes-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Determinants of Satisfaction of Users of Electronic Banking Services

Abstract: Under the conditions of increased competition, imperatives for banking institutions are focusing on the provision of better quality services, meeting the needs of clients and adjusting to their specific demands, as these are the conditions for achieving satisfaction. Satisfaction has a consequent effect on the realisation of communication, but also economic business goals of market players. In accordance with these facts, the significance of measuring the quality of services needs to be pointed out. In recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
1
2
0
1
Order By: Relevance
“…Results of the research showed that satisfaction of the bank clients is most strongly determined by empathy and the weakest by tangibility, that is, by the interior and exterior of the bank, the appearance of employees and so on. An interesting result is that dimension reliability that relates to understanding clients' problems and compliance with agreed deadlines has no statistically significant influence on clients' satisfaction, which is consistent with results of the research by Gasevic et al (2016), but opposite to the results of Al Afeshat & Alola (2018) which confirmed that there is statistically significant influence of all dimensions of SERVQUAL model on clients' satisfaction. On the other hand, clients' loyalty is most strongly influenced by responsiveness, and the weakest is, as well as satisfaction, under the influence of tangibility.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Results of the research showed that satisfaction of the bank clients is most strongly determined by empathy and the weakest by tangibility, that is, by the interior and exterior of the bank, the appearance of employees and so on. An interesting result is that dimension reliability that relates to understanding clients' problems and compliance with agreed deadlines has no statistically significant influence on clients' satisfaction, which is consistent with results of the research by Gasevic et al (2016), but opposite to the results of Al Afeshat & Alola (2018) which confirmed that there is statistically significant influence of all dimensions of SERVQUAL model on clients' satisfaction. On the other hand, clients' loyalty is most strongly influenced by responsiveness, and the weakest is, as well as satisfaction, under the influence of tangibility.…”
Section: Resultssupporting
confidence: 55%
“…When considering dependence between service quality dimension and satisfaction of banks' clients, Van Quyet et al (2015) as well as Rijwani et al (2017) came to the conclusion that all five dimensions of the SERVQUAL model have statistically significant influence on customer satisfaction. Using a modified SERVQUAL model for measuring electronic banking services quality in Serbia, Gasevic et al (2016) confirmed the influence of security, ease of use and responsibility on satisfaction, while reliability, empathy and website content have non-significant influence on satisfaction.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Najveće ograničenje obimnijeg korišćenja usluga elektronskog bankarstva je nedostatak poverenja klijenata banaka u sigurnost obavljanja ovakvih transakcija [28]. Pored sigurnosti i poverenja [29; 30], značajan uticaj na zadovoljstvo i povećanje broja korisnika ima i jednostavnost korišćenja usluga elektronskog bankarstva [31]. Na poverenje klijenata u usluge elektronskog bankarstva najveći uticaj imaju kvalitet elektronskih usluga, kao što su jednostavnost korišćenja, privatnost i sigurnost, individualne karakteristike klijenata, kao što su individualna sklonost poverenju, kao i karakteristike banke, kao što su reputacija, veličina i zavisnost od države [32].…”
Section: Trenutno Stanje I Trend Razvoja Elektronskog Bankarstva U Sr...unclassified
“…Therefore, maintaining quality is the key to success in online baking (Nochai & Nochai, 2013;Yi, 2014). Under increased competition, banking institutions' imperatives focus on providing better service quality, meeting clients' needs and adjusting to their specific demands, as these are the conditions for achieving customer satisfaction (Gasevic et al, 2016). Since traditional banking services have unique delivery processes, their quality will be difficult to be applied to online banking.…”
Section: Introductionmentioning
confidence: 99%